Extraction of waterborne prostaglandins from female goldfish, Carassius auratus (Linnaeus) - Ghumare, S S; Jagtap, H S; Borate, H B; Wakcharkar, R D; Ravindranathan, T (Indian Journal of Fisheries, 2011)
An effective method for the analysis of large volumes of dilute aqueous samplesfor biological studies, consisting of a simple device for extraction of organic constituentsis described. The utility of the present method is demonstrated by theanalysis of waterborne prostaglandins from the Tiaprost-administered goldfish,Carassius auratus.